Respuesta :

Answer:

4). [tex] x^{3} +5x+18 [/tex]

Step-by-step explanation:

The binomial (x+2) is a factor of [tex] x^{3} +5x+18. [/tex]

Since, (x + 2) is a factor.

So, x = - 2 is a root

Plug x = - 2 in [tex] x^{3} +5x+18 [/tex]

We find:

[tex] x^{3} +5x+18 [/tex]

[tex] =(-2)^{3} +5(-2)+18 [/tex]

[tex] =-8 - 10+18 [/tex]

[tex] = - 18+18 [/tex]

[tex] = 0 [/tex]

Since, at x = - 2 the value of the expression [tex] x^{3} +5x+18 [/tex] becomes zero.

Therefore, (x + 2) is a factor of [tex] x^{3} +5x+18 [/tex]